8 - Book Reviews: Michel Ben Arrous, 2003, Coalition, Dispersion. Un moment démocratique en Afrique de l’Ouest « francophone», 1988-1998, CODESRIA, Dakar.: by Alawadi Zelao - Journal system (Africa Development, 2022)
Alawadi Zelao, Sociologue/Chercheur Centre National d'Education BP 1457, Yaoundé, Cameroun